Anatomical-embryological correlates in atrioventricular septal defect. Issue 5 (May 1982) - Allwork, S P
Abstract : Recent embryological studies have supported the consideration that the ventricular septum is multifocal in origin. These data have also provided excellent correlation of the morphology of malformed hearts with their embryology. In particular, atrioventricular septal defect correlates accurately with these observations on ventricular septation. Many of the names given to atrioventricular septal defect (for example ostium primum, persistent atrioventricular canal, endocardial cushion defect) indicate attempts at correlating the anatomy with embryology. None of these has been very convincing. In the light of this uncertainty, this review considers briefly the anatomy of the malformation and its ontogeny, and presents a hypothesis of the development of atrioventricular septal defect. Although there is almost always a communication above the atrioventricular valves, the malformation lies in the ventricular, not the atrial septum. Hearts with inlet septal defect without interatrial communication represent one end of the spectrum of anomalies, and those with common atrioventricular orifice, in which Fallot's tetralogy or single outlet heart may be associated, mark the other end. The outflow tract malformations are not randomly associated, but are points in a huge range of cardiac malformations.